Impact of restrictions due to COVID-19 on a quality-assured screening colonoscopy program - Hinterberger, Anna; Jiricka, Lena; Waldmann, Elisabeth A.; Penz, Daniela; Majcher, Barbara; Asaturi, Arno; Szymanska, Aleksandra; Rockenbauer, Lisa; Ferlitsch, Arnulf; Trauner, Michael H.; Ferlitsch, Monika (Endoscopy International Open, 2021)
Background and study aims On February 25, 2020, the first patient was diagnosed with COVID-19 in Austria. On March 16, 2020, the Austrian government imposed restrictions and subsequently the Austrian Medical Association recommended minimizing screening examinations in compliance with government restrictions. The aims of this study were to evaluate the impact of this recommendation on the number of colonoscopies performed weekly and detection of non-advanced adenomas, advanced adenomas (AA) and colorectal cancer (CRC) and to calculate how many undetected adenomas could have developed into CRC.Methods We analyzed the number of colonoscopies and pathological findings within a quality assured national colorectal cancer screening program before the COVID-19 pandemic (March 1,t 2019 to September 1, 2019, Period 1) and compared those rates to months during which access to colonoscopy was limited (March 1, 2020 and September 1, 2020, Period 2) with a Wilcoxon-rank-test and a chi-square test.Results A total of 29,199 screening colonoscopies were performed during Period 1 and 24,010 during Period 2. The mean rate of colonoscopies per week during Period 1 was significantly higher than during Period 2 (808,35 [SD = 163,75] versus 594,50 [SD = 282,24], P = 0.005). A total of 4,498 non-advanced adenomas were detected during Period 1 versus 3,562 during Period 2 (P < 0.001). In total 1,317 AAs and 140 CRCs were detected during Period 1 versus 919 AAs and 106 CRCs during Period 2. These rates did not differ significantly (P = 0.2 and P = 0.9).Conclusions During the COVID-19 crisis, the number of colonoscopies performed per week was significantly lower compared to the year before, but there was no difference in the detection of CRCs and AAs.